Early immune recovery after autologous transplantation in non-Hodgkin lymphoma patients: predictive factors and clinical significance. Issue 9 (1st September 2016) - Valtola, Jaakko; Varmavuo, Ville; Ropponen, Antti; Selander, Tuomas; Kuittinen, Outi; Kuitunen, Hanne; Keskinen, Leena; Vasala, Kaija; Nousiainen, Tapio; Mäntymaa, Pentti; Pelkonen, Jukka; Jantunen, Esa
Abstract: Limited data is available about the factors affecting early immune recovery or its clinical significance after autologous stem cell transplantation (auto-SCT). We prospectively analyzed factors affecting early immune recovery and outcome among 72 non-Hodgkin lymphoma (NHL) patients. Absolute lymphocyte count 15 d after auto-SCT (ALC-15) ≥ 0.5 × 10 9 /L was associated with the use of plerixafor ( p = 0.004), the number of CD34 + cells ( p = 0.015), and CD34 + CD38 − cells ( p = 0.005) in the grafts. ALC-15 ≥ 0.5 × 10 9 /L was associated with improved overall survival ( p = 0.021). In patients with aggressive histology, ALC-15 ≥ 0.5 × 10 9 /L was beneficial in regard to both progression-free survival ( p = 0.015) and overall survival ( p = 0.002). Early immune recovery seems to be important in transplanted patients with NHL and, therefore, an easy and affordable method for disease-related risk analysis. Patients with aggressive histology and slow immune recovery may need additional post-transplant treatment.